The social architecture of French cinema, 1929-1939 - Flinn, Margaret C. (Contemporary French and francophone cultures, 2014)
This book provides a vital new reading of documentary and realist fiction film of the French 1930s that focuses on how these genres interlock their representations of urban spaces and places.